2022
DOI: 10.3389/fpsyg.2022.1015590
|View full text |Cite
|
Sign up to set email alerts
|

Informal science, technology, engineering and math learning conditions to increase parent involvement with young children experiencing poverty

Abstract: Broadening participation in early science, technology, engineering and math (STEM) learning outside of school is important for families experiencing poverty. We evaluated variations of the Teaching Together STEM pre-kindergarten program for increasing parent involvement in STEM learning. This informal STEM, family engagement program was offered in 20 schools where 92% of students received free/reduced lunch. The core treatment included a series of family education workshops, text messages, and family museum pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 25 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…There were small, non-significant increases (ES = 0.18) in parents’ reported frequency of STEM involvement. Although non-significant, effect sizes were similar in magnitude to past, in-person versions of this program ( ES range − 0.08 to 0.18 at posttest; Zucker et al, 2022 ). On the one hand, these similar magnitudes of impacts on parent behaviors for in-person and virtual modalities may indicate that both approaches are suitable.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…There were small, non-significant increases (ES = 0.18) in parents’ reported frequency of STEM involvement. Although non-significant, effect sizes were similar in magnitude to past, in-person versions of this program ( ES range − 0.08 to 0.18 at posttest; Zucker et al, 2022 ). On the one hand, these similar magnitudes of impacts on parent behaviors for in-person and virtual modalities may indicate that both approaches are suitable.…”
Section: Discussionmentioning
confidence: 57%
“…The materials mailed to families were exactly the same as the in-person funshop materials mentioned in our study, but we selected a portion of past materials because we only delivered four of the six available workshop themes in this brief virtual intervention. We also did not send the nine supplemental materials given in two groups of our prior study (B and C; Zucker et al, 2022 ) because that would have resulted in a likely overwhelming number of activities for parents to use and because the cost of mailing these exceeded typical museum outreach budgets. The text messages and facilitators in modeling videos were exactly the same as in our initial study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study considered if hybrid delivery of a STEM family engagement program was an accessible and effective means of increasing parent involvement and child STEM enthusiasm during the 3-and 4-year-old pre-kindergarten (pre-k) period. This experiment was a conceptual replication of a museum outreach program focused on broadening STEM access for families experiencing poverty, which we evaluated when delivered in person (Zucker et al, 2022), virtually (Zucker et al, 2024), and here with a hybrid approach. We previously found that families' in-person attendance was challenging due to limited time and scheduling conflicts (Zucker et al, 2022).…”
Section: Introductionmentioning
confidence: 99%